2022
DOI: 10.1021/acsami.2c03250
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial Ceramic Direct Ink Writing on Heterogenous and Rough Surfaces: Investigation of Core–Shell Interactions

Abstract: In this work, coaxial conductor–ceramic direct ink writing enables the printing of sensitive or encapsulated materials onto heterogeneous and rough substrates. While encasing the core fluid within a stiff ceramic shell, continuity may be maintained, even while printing onto conventionally challenging substrates. Here, we report the development of a coaxial ceramic direct ink writing suite and explore coflow interrelationships based on microfluidic principles. A coaxial nozzle is designed to facilitate the coex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The ratio of major and minor axes of the printed core structure displays 1.034 (Figure S5a), which is close to a perfect circle. This can be supported by the dimensionless quantity, Ξ: , normalΞ = τ normaly ρ g h + γ R 1 where τ y and ρ are the dynamic yield stress and density of the Ag ink respectively, γ is the interfacial tension between the core Ag ink and shell epoxy ink, and R is the core radius. In our case, the calculated Ξ is ∼2.24 (details in Supporting Information), indicating that the dynamic yield stress of Ag ink is enough to resist the potential deformations caused by the gravitational pressure and capillary forces.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…The ratio of major and minor axes of the printed core structure displays 1.034 (Figure S5a), which is close to a perfect circle. This can be supported by the dimensionless quantity, Ξ: , normalΞ = τ normaly ρ g h + γ R 1 where τ y and ρ are the dynamic yield stress and density of the Ag ink respectively, γ is the interfacial tension between the core Ag ink and shell epoxy ink, and R is the core radius. In our case, the calculated Ξ is ∼2.24 (details in Supporting Information), indicating that the dynamic yield stress of Ag ink is enough to resist the potential deformations caused by the gravitational pressure and capillary forces.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Material extrusion-based additive manufacturing enables the ability to selectively dispense multiple materials in three-dimensional space with custom chemistries and architectures. , Fused deposition modeling (FDM) has been demonstrated as a viable process to generate multimaterial radiation shields. The integration of shields produced via FDM, however, requires separate assembly steps as the processing temperatures of extrusion and poor adhesion to microelectronics prevent the direct deposition of shielding onto devices. ,,, Conversely, direct ink writing (DIW) additive manufacturing enables the deposition of composite inks with high volumetric loading of additives. Depending on the binder chemistry, inks can be printed at room temperature and be conformally deposited on a wide range of substrates. , Furthermore, DIW enables architecture modification of filaments into core-shell, graded, and blended additive structures. FDM printing has also demonstrated the ability to make core-shell architectures, although the requirements for fabrication limit the volumetric loading of inorganic particle additives. Furthermore, the processing conditions require 3D printing of preforms with two materials which are then thermally drawn into core-shell filaments or melt extrusion of two polymer feedstocks which prevent adhesion directly onto electronics. Brounstein et al have shown that DIW can be used to produce shielding against neutron radiation that could also readily dissipate heat from the shielded device .…”
Section: Introductionmentioning
confidence: 99%
“…Multi-material DIW based on fluidic strategy is executable. But due to complex extrusion control [5,[47][48][49][50], it presents limitations on producing functional filaments or products with complicated shapes.…”
Section: Introductionmentioning
confidence: 99%